Frames of Immigration Justice in U.S. University Responses to the Travel Ban - Stein, Sharon (ACME: An International Journal for Critical Geographies, 2018)
This article analyzes U.S. university presidents’ public responses to the Trump administration’s first travel ban in January 2017. Within these responses, most presidents voiced their support for international students, staff, and faculty. However, it remains necessary to consider the discursive frames through which this support is articulated. I found that support for international members of the campus community was largely expressed in ways that implicitly naturalized the regulation of immigration according to racialized assessments of human value. This article considers the role of universities in reproducing and/or interrupting the logics and practices of white supremacy, capitalism, and nationalism, and the limits of responses to the ban that are framed through discourses of conditional inclusion and perceived contributions to the campus and country.